Dynamic Global Currency Hedging. (24th March 2021) - Christensen, Bent Jesper; Varneskov, Rasmus Tangsgaard
Abstract: This article proposes a model for discrete-time currency hedging based on continuous-time movements in portfolio and foreign exchange rate returns. The vector of optimal currency exposures is given by the negative realized regression coefficients from a one-period conditional expectation of the intraperiod quadratic covariation matrix for portfolio and exchange rate returns. Empirical results from an extensive hedging exercise for equity investments illustrate that currency exposures exhibit important time variation, leading to substantial volatility reductions when hedging, without sacrificing returns. A risk-averse investor is willing to pay several hundred annual basis points to switch from existing hedging methods to the proposed dynamic strategies.